THE METHODOLOGY FOR IMPLEMENTING EDUCATIONAL SOFTWARE FOR TEACHING NATURAL SCIENCES IN GRADE 6 BASED ON AN INTEGRATIVE APPROACH - Baxtiyoriy Madinabonu Baxtiyor qizi (Modern American Journals, 2025)
Based on an integrative approach, the aim is to demonstrate the connection between the knowledge, skills, and competencies acquired by 6th-grade students and their daily lives through lessons and extracurricular activities. This involves conducting educational research, performing experiments, fostering creativity aimed at project development, and cultivating students’ interest in creating innovations.
Keywords: Natural sciences, knowledge, skills, competency, scientific competence, practical competence, researcher, integrative approach.